DETERMINATION RISK OF BREMSSTRAHLUNG RADIATION PRODUCED BY BETA-RAY - Jarallah, Naz (Malaysian Journal of Science, 2024)
When interacting with absorption materials, beta rays, which are emitted by isotopes, are harmful because bremsstrahlung (braking) radiation is produced. Therefore, the efficiency of a shielding material can be improved by considering the bremsstrahlung radiation generated by the material’s beta ray absorption. In this study, to determine the risk of bremsstrahlung radiation produced by beta rays, the fractions of beta energy transformed into bremsstrahlung radiation were calculated for beta emitters in the energy ranges of 0.0026–0.1734, 0.205–0.694, and 0.9345–2.640 MeV, using five different absorption materials (13Al, 26Fe, 48Cd, 74W, and 82Pb). The relationship between the fractions of beta energy transformed into bremsstrahlung radiation by the five shielding materials and the maximum energies of some beta emitters was studied to determine the most suitable beta-ray shielding materials to effectively minimize bremsstrahlung radiation. The results showed that the fractions of beta energy transformed into bremsstrahlung radiation increased as the beta energy and the atomic number of the shielding material increased. The fraction of beta energy transformed into bremsstrahlung radiation in 13Al ˂ 26Fe ˂ 48Cd ˂ 74W ˂ 82Pb.Therefore, beta ray shields should be made with low atomic number materials to reduce the generation of bremsstrahlung radiation. Practically, beta shields made from materials with atomic numbers greater than 13 are rarely employed; notably, aluminum successfully decreased the production of bremsstrahlung radiation. However, it is also necessary to use materials with medium and high atomic numbers as secondary beta shields to reduce the effect of the bremsstrahlung radiation photons formed by the interaction between beta rays and shielding materials.